Internet As A Medium For Commodity Branding - The Case Of Malaysian Palm Oil - Abdul Rahman, Mohammad Hafezh (2009)
This paper will discuss on various branding efforts and theories, and define them to be the most suitable for commodity branding. From there, a match with the internet technology functionalities will be done to capitalize on this explosive marketing channel in today's world.